The quality of higher education of theology in front of the challenges of the 21st century - Rodrigues, Marilze Wischral; Rodrigues, Stélio João (Vox Scripturae - Revista Teológica Internacional, 2016)
This research takes place in view of the recent discussion on the regulation of undergraduate degree in Theology, with the higher education legislation in Brazil. It aims: a) to investigate the criteria of higher education courses in Theology; b) to identify the contributions of the Resolution n. 4 of 16th September 2016, for the structuring of higher education courses in theology; c) to describe the requirements of resolution n. 4 of 16th September 2016, in the face of higher education institutions offering degrees in Theology. The main principle of education is to contribute to the human being by his full development as a person, including their spirituality and theological knowledge. Theological education in the perspective of Christian faith, considering the need for interreligious dialogue, has an open and ongoing task in defense of life, as a greater good, absolute, even in a relativizing society. The quality of theological education institutions is built by the commitment to the surrounding reality and efficiency in action for the reached and empowered people. This Article reviews documents of the National Council of Education, related to higher education courses in Theology. It can be observed that progress has been made in the organization and implementation of superior theology course in higher education institutions in Brazil. There is still a process to be followed to put into practice the National Curriculum Guidelines. But a minimum Curriculum can be found and be used to qualify the higher courses of Theology, in higher education institutions that wish to be considered serious and having a high quality.
Keywords: Theological education; Higher education; Quality; 21st Century